Kondisi Sosial dan Alam Papua Dalam Puisi "Angin-Angin Laut Irian" Karya Diah Hadaning - Nisrina Putri Suheri; Emma Marsela (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
Diah Hadaning's poem "Angin-Angin Laut Irian" lists the social and natural conditions in Papua as a form of his criticism of the changes and environmental destruction that occurred. This analysis further describes the meaning implied in the poem using descriptive qualitative methods. Diah Hadaning highlighted the environmental damage that then affected the social conditions of Papuan people. In his poetry, Diah Hadaning expressed many of his concerns about the survival and traditions of Papuan society. The analysis showed that Hadaning's work was not only used as a literary work, but as a form of criticism and concern for the state of the region that had begun to lose their identity. Keywords: Social criticism, Papua.